Descriptive Study on Demographic Factors and Performance Strategies Among Athletes - Nor Mazlina, Ghazali; Norsiah, Fauzan; Anuar, Ayob; Edris, Aden (Human Resource Management Academic Research Society (HRMARS), 2018)
The purpose of this research was to investigate the differences between demographic factors and performance strategies among athletes. The demographic factors such as gender, years of study, and years of involvement in sports play an important role in the use of performance strategies in determining their performance strategies in sports. The instrument used for this research was the Test of Performance Strategies (TOPS) to measure the performance strategies. The finding has shown that there were significant differences between the demographic factors and the performance strategies. The demographic variables consist of age, gender, year of study, and years of involvement in sports. The performance strategies include the constructs (goal setting, relaxation, activation, imagery, self-talk, attentional control, emotional control, and automaticity). In general, the result showed that the differences between the demographic factors such as; gender at t (21) = 13.75; p < .05; years of study at t (21) = 9.46; p < .05 and years of involvement at t (20) = 11.37; p < .05 and the performance strategies were significant. In addition, there were significant differences between the demographic factors (age, gender, year of study, and years of involvement in sports) and all sub factors in the performance strategies such as goal setting, relaxation, activation, imagery, selftalk, attentional control, emotional control, and automaticity. Based on the findings, it can be inferred that to enhance the athletes’ ability and competency in sports, they have to be trained in various styles/methods according to their age, gender, years of study, and years of involvement.